Performance and emission analysis of compression ignition engine using biodiesels from Acid oil, Mahua oil, and Castor oil. Issue 2 (15th December 2019) - Kareemullah, Mohammed; Afzal, Asif; Fazlur Rehman, K.; Shahapurkar, Kiran; Khan, Hurmathulla; Akram, Naveed
Abstract: Research on and use of biodiesels for engines is growing continuously in the present era. Compression ignition (CI) engine performance for biodiesels of blends B20 from Acid oil, Mahua oil, and Castor oil is experimentally investigated. The engine performance analysis in the form of brake‐specific fuel consumption, brake‐specific energy consumption, brake thermal efficiency (BTE), exhaust gas temperature (EGT), and air fuel ratio are compared with diesel as base fuel. Emission characteristics like CO, CO2, NOx, and opacity are comparatively studied in detail for the considered biodiesels. The entire study is compared with the performance of engine when pure diesel is chosen as fuel. From the complete analysis it was observed that the BTE was higher for Acid oil and Mahua oil among the biodiesels used. And regarding CO emissions, Mahua oil showed lower effect than other biodiesels. Upto 6% increase in EGT of Mahua oil was obtained at no load and for other loads the percent reduced. For all the biodiesels the % enhancement in Co, CO2, and NOx was more than 60% at highest load compared with diesel.